2013
DOI: 10.1128/aac.00714-13
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Linezolid and Daptomycin for Treatment of Vancomycin-Resistant Enterococcal Bloodstream Infections

Abstract: Bloodstream infections due to vancomycin-resistant enterococci (VRE-BSI) result in substantial patient mortality and cost. Daptomycin and linezolid are commonly prescribed for VRE-BSI, but there are no clinical trials to determine optimal antibiotic selection. We conducted a systematic review for investigations that compared daptomycin and linezolid for VRE-BSI. We searched Medline from 1966 through 2012 for comparisons of linezolid and daptomycin for VRE-BSI. We included searches of EMBASE, clinicaltrials.gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 42 publications
2
46
1
2
Order By: Relevance
“…Supporting this proposal is the fact that daptomycin is recommended in addition to vancomycin in cases of MRSA bacteremia according to the current guidelines proposed by the Infectious Diseases Society of America for the treatment of MRSA infection, despite the absence of absolute superiority of this drug over vancomycin in patients with bone and joint infections (34,35). Of note, the superiority of daptomycin over linezolid for treating vancomycinresistant enterococcal infections is not clear, although the need for long-term administration suggests that daptomycin is more desirable than linezolid (36). However, daptomycin should be used appropriately, as a daptomycin-resistant enterococcal strain has previously been reported (37).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this proposal is the fact that daptomycin is recommended in addition to vancomycin in cases of MRSA bacteremia according to the current guidelines proposed by the Infectious Diseases Society of America for the treatment of MRSA infection, despite the absence of absolute superiority of this drug over vancomycin in patients with bone and joint infections (34,35). Of note, the superiority of daptomycin over linezolid for treating vancomycinresistant enterococcal infections is not clear, although the need for long-term administration suggests that daptomycin is more desirable than linezolid (36). However, daptomycin should be used appropriately, as a daptomycin-resistant enterococcal strain has previously been reported (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published meta-analyses revealed increased survival with linezolid compared to that with daptomycin (18,19). One explanation for the differences in the findings in these studies compared to the current one is that these prior studies included In the financial data cohort, 33 (91.7%) subjects within the daptomycin group were matched to 33 (31.4%) within the linezolid group; 23 (63.9%) subjects in the daptomycin group were matched to 23 (41.8%) in the ␤-lactam group; and 46 (43.8%) subjects in the linezolid group were matched to 46 (83.6%) subjects in the ␤-lactam group.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for VRE colonization include underlying diseases such as chronic renal failure, diabetes mellitus, cardiovascular disease and dialysis 25 . Development of VRE colonization can lead to a lifethreatening complication especially in the immunosuppressed patients 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Pan et al, long stay in the intensive care unit was found as a major risk factor for VRE colonization 22 . VRE colonization 9,25 . In our study, use of antibiotic was found to be significantly higher in the rectal colonization group compared to the non-colonized group.…”
Section: Discussionmentioning
confidence: 99%